ANALISIS DAMPAK ALIH FUNGSI LAHAN PERTANIAN KE NON PERTANIANTERHADAP KETAHANAN PANGAN DI KECAMATAN GONDANGREJO KABUPATEN KARANGANYAR TAHUN 2011 – 2020 - Desi Kumalasari; Sarwono; Rita Noviani (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2023)
The ever-increasing population growth and the construction of various public facilities have led to the conversion of agricultural land in Gondangrejo District. With the conversion of agricultural land functions, it can threaten the food security of the population in the region. This study aims to: (1) Find out about land conversion in Gondangejo District in 2011–2020. (2) Knowing the level of food security of the population in Gondangrejo District. (3) Evaluating the impact of land conversion on the food security of the population in Gondangrejo District in 2020. This research uses a qualitative method. Data collection techniques are carried out by observation and data collection. The data analysis technique uses descriptive qualitative analysis. The results of this study are (1) Interpretation of remote sensing imagery in 2011, 2015, and 2020 shows the results of the conversion of agricultural land in Gondangrejo District, where the use of paddy fields in 2011 was 4,037.71 ha or around 66.5% to 1,903, 90 ha or around 31.04% of the total area of land use in Gondangrejo District, so that the conversion of paddy fields that occurred was 2,133.81 ha or around 52.85%. (2) The average population food security for Gondangrejo District is food security. Because there is a surplus value of food availability of 1,323.76 tons or 15.28% of the value of 100% food needs. (3) The impact of changing the function of paddy fields causes a decrease in rice production by an average of 694.91 tons/year. However, the food security of the population is maintained despite land conversion. The T-test shows that there is a significant difference in the level of food needs between before and after land conversion occurs.